Exploration of In-situ Leaching Technology and Effectiveness of Hadatu Sandstone-type Uranium Mine Based on Analogy Method - ZHOU Yiru1, 2, YANG Yihan2, ZHANG Chuanfei2, YAO Guanghuai2, QIAO Peng2, REN Xiaoping2, XIA Liangshu1, (Yuanzineng kexue jishu, 2025)
Both Hadatu and Bayanwula belong to the ancient valley sandstone uranium mines in the upper part of the Saihan period in the Erlian basin, with the same ore-bearing stratigraphy and lithology, and there are both similarities and differences. Bayanwula uranium mine has been mined on a large scale, and the parameters of the stable ground leaching uranium process have mastered. In order to better learn from the Bayanwula uranium mining experience, explore Hadatu uranium mining process parameters and effects, in this paper, the similarities and differences between Hadatu and Bayanwula uranium mines in terms of mine geology, hydrogeological conditions and process mineralogy were compared. The results show that the continuation of Hadatu uranium mine body is better, the carbonate content is 0.14%-0.46%, which is similar to the carbonate content of Bayanwula, both are lower, and similar acid leaching process can be used. The average grade of Hadatu uranium mine body is higher than that of Bayanwula, and the permeability coefficient is smaller than that of Bayanwula, so the dilution effect of the leaching process is weakened, which helps the leaching of uranium mine, and the mining conditions are generally better than those of Bayanwula. Hadatu uranium mine pressurised head height is greater than Bayanwula uranium mine, water level depth is less than Bayanwula uranium mine, ground leaching mining process to help leach solution upgrading. The ore body of Hadatu uranium mine is deeper and thinner, but with higher grade and higher metre percentage, the quality of the ore is relatively better. The ore indoor ground leaching process test shows that Hadatu and Bayanwula uranium mines have the same uranium leaching law, the ore samples are suitable for acid leaching, and have a good leaching rate, in which the leaching agent acidity is 10 g/L, the residue meter leaching rate is the largest, and the leaching process is the most economical. The leaching cycle of Hadatu uranium mine is shortened by increasing leaching agent acidity, the liquid-solid product mass ratio decreases, the peak uranium mass concentration and average uranium mass concentration increase, but the acid consumption of tonnes of ore and tonnes of uranium increases significantly, the raw material consumption increases, and the cost of mining increases. Based on the results of geological, hydrogeological and indoor ground leaching process tests, the field test of Hadatu uranium mine is proposed to adopt the acid leaching process, and the recommended acidity of leach agent is 10 g/L.